Leadership, a practical guide to theory and practice - Henry, B. Charles ([Createspace], 2010)
Leadership is a highly debated topic in contemporary America and around the world. The mystery of leadership and in particular, good leadership has long been debated by respective civilizations for centuries. Respected authors throughout the history of modern man have posited many theories and new theories continue to emerge though scholarly and practical examination of hypotheses as modern societies search for new and improved ways of accomplishing effective leadership.